باقیاتِ اقبال'' از ڈاکٹر سیّد تقی عابدی تحقیقی و تنقیدی مطالعہ : “Baqiyat e Iqbal” by Dr. Syed Taqi Abidi: A research and critical study - Riaz, Muhammad (Tashkeel e Jadeed, 2026)
This article presents a critical and analytical study of Baqiyat-e-Iqbal, compiled by Dr. Syed Taqi Abedi, which aggregates Allama Iqbal’s neglected and discarded poetic works. The research evaluates the compilation’s thematic and stylistic coverage—including ghazals, poems, rubaiyat, and Persian verses—against the backdrop of earlier scholarly milestones by figures such as Sabir Kalorvi, Gyan Chand, and Abdul Waheed Mu’ini. Through comparative textual analysis, the study assesses Dr. Abedi’s editorial methodology and the work's contribution to modern Iqbal scholarship. The findings reveal that while Abedi’s Baqiyat-e-Iqbal serves as a significant editorial enterprise, it functions primarily as a redaction of existing collections rather than a source of original critical discovery or rigorous textual re-examination. Ultimately, this paper situates Dr. Abedi’s work within the continuum of Iqbaliyat, reaffirming the foundational importance of prior compilers in preserving Iqbal’s abandoned literary heritage